Organophosphorous poisoning complicated with intermediate syndrome- A case reprt - Hussain, Asraf; Adhikari, Krishna (Journal of Advances in Internal Medicine, 2020)
Organophosphorous poisoning is a very common poisoning. Intermediate syndrome with respiratory failure is a highly fatal complication. We report a case of 20 year old male who developed intermediate syndrome despite adequate atropinisation . Early clinical recognition of the syndrome and institution of mechanical ventilation along with ongoing atropine therapy was instrumental in saving the patient’s life. Patient was discharged on day 10 after successful treatment.